3 DEGREES OF FREEDOM REHABILITATION ROBOT DESIGN AND TRAJECTORY CONTROL FOR UPPER LIMB - CESARIO ZUHRI (NIM : 13313038) - ARDA PUTRA RYANDIKA (NIM : 13313082), ARDANI
The percentage of people who suffer from stroke keep on increasing each year. One of the body parts that can suffer from a stroke is the arm. To reduce the number of the victims, a rehabilitation robot that can effectively cure a paralyzed patient is needed. The development of rehabilitation robot also has another purpose, and that is to reduce doctor's work in rehabilitation processes resulting in more patients that can be treated. This study aims to design a rehabilitation robot capable of moving with 3 degrees of freedom (DOF) and perform repetitive movements to increase the consistency of the rehabilitation process. The robot is designed by using 3 revolute joints to perform the 3 degrees of freedom movement. In addition, the robot is controlled by using trajectory control. Trajectory control can determine the path for the machine to go through from the starting position to the end position. With the addition of a mechanism that can compensate the dynamic of the robotic arm, the machine can move more perfectly and the time it takes for the machine to complete the motion becomes shorter. The limits of movement that the rehabilitation robot can perform are in the range of values 282≤𝑟≤1259,−45≤𝜃≤45,−4≤𝜙≤86, With r values in mm, ϕ and θ in degrees. According to the experiment's results, the control system that didn't include the compensation mechanism failed to achieve the desired set point and has a sum squared value of 1.23 m2. On the contrary, the control system that includes the compensation mechanism has succesfully achieved the desired set point in 4.35 seconds and with a sum squared error (SSE) value of 0.30 m2. Lastly, the robot has also successfully completed the repetitive movement for 10 times, with the SSE value of 0.32 m2 for each repetition.